2009
DOI: 10.1080/00207450802324127
|View full text |Cite
|
Sign up to set email alerts
|

Thought Disorder and Executive Dysfunction in Patients with Schizophrenia

Abstract: Although, impairment of executive functioning is often reported in schizophrenia, its association with thought disorder has not been fully determined. The present study examined the relationships between positive thought disorder assessed using the Harrow's Thought Disorder Scale (Harrow's scale) and executive function by Wisconsin Card Sorting Test (WCST) in 27 inpatients with schizophrenia. Age at onset exhibited a significant negative correlation with Wechsler Adult Intelligence Scale comprehension test sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Patients with schizophrenia show deficit on all of the measures compared with normal controls. [11,12] In a study of 31 chronic schizophrenic patients, 2 variables on the WCST (viz., the number of categories completed and percent perseverative response) were found to significantly discriminate between subjects of high versus low awareness. [8] In another study, the researchers administered the WCST and repeated the test over a period of 1 year on the patients of schizophrenia with unimpaired insight.…”
Section: Original Arti Clementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with schizophrenia show deficit on all of the measures compared with normal controls. [11,12] In a study of 31 chronic schizophrenic patients, 2 variables on the WCST (viz., the number of categories completed and percent perseverative response) were found to significantly discriminate between subjects of high versus low awareness. [8] In another study, the researchers administered the WCST and repeated the test over a period of 1 year on the patients of schizophrenia with unimpaired insight.…”
Section: Original Arti Clementioning
confidence: 99%
“…Patients with schizophrenia show deficit on all of the measures compared with normal controls. [1112]…”
Section: Introductionmentioning
confidence: 99%
“…While Owashi, Iwanami, Nakagome, and Higuchi (2009) found no significant relationship between thought disorder and executive functioning in schizophrenic patients, Nestor et al (1998) found that thought disorder was significantly and negatively correlated with performance on an executive functioning and verbal memory tasks. However, the relationship between thought disorder and neurocognitive functioning has not been thoroughly investigated, and it warrants further study.…”
Section: The Relationship Between Thought Disorder and Neurocognitivementioning
confidence: 95%
“…The relationships between depressive symptoms and neurocognition in schizophrenia as examined in Halari et al (2006); between affect and thought disorder as indirectly examined in Jamapala et al (1985Jamapala et al ( , 1989 and Osher and Berdusky (2007); and between thought disorder and neurocognitive functioning as examined by Owashi et al (2009) and Nestor et al (1998) have yet to be more firmly established. However, the implications of these findings suggest that these three variables share a complex relationship.…”
Section: Direction and Purpose Of The Investigationmentioning
confidence: 99%
“…Estos déficits están presentes (no siempre en igual intensidad) en los diferentes subtipos clínicos de la enfermedad y ha sido ampliamente documentado pese a que ha sido en las últimas décadas cuando ha comenzado su estudio sistemático y en profundidad. El grado de deterioro cognitivo se encuentra además relacionado con una inferior calidad de vida del paciente (Cruz, 2010), así como de sus familiares (Grandón, 2001;Cruz, Jenaro, Pérez y Flores, 2010 (Owashi, Iwanami, Nakagome, Higuchi, Higuchi, y Kamijima, 2009).…”
Section: Figura 3 Déficits Neurocognitivos En Pacientes Con Esquizofunclassified